Governance and Investment of Public Pension Assets : Practitioners' Perspectives - Rajkumar, Sudhir (World Bank, 2012)
The impact of good governance on investment management and performance is immense. Several key factors contribute to good governance within pension funds, appropriate governance structures; well-defined accountabilities, policies, and procedures; and suitable processes for the selection and operation of governing bodies and managing institutions. Not surprisingly, good governance requires leadership by individuals with the expertise, professionalism, and integrity to navigate a fund's direction and withstand pressures from multiple constituencies. In the current context of aging populations in many countries, fiscal burdens on pension funds are increasing. At the same time, the necessity of delivering on pension commitments in contributory schemes means that governance, transparency, and accountability should be of utmost importance to pension fund managers. With these concerns in mind, part three of this book provides useful perspectives from senior managers of public pension funds, international pension authorities, and multilateral institution representatives on the structures, policies, and processes that aim to support good governance. Principally reflecting on the characteristics that have been conducive to good governance, including reform measures undertaken, they also consider policy and investment management measures taken to effectively manage fiscal risks, including those that emerged from the financial crisis.